(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The obtaining of hybrid mineral polymer sorbents, based on wide-porous microspherical silica gels and polymer components, has been discussed. The possibility to apply the obtained sorbents in reversed-phase high performance liquid chromatography has been confirmed. Introducing the polymer layer onto the surface of microspherical silica gel has been realized by means of “dry polymerization” of corresponding monomers in the adsorbed layer of the porous matrix surface.